Revenue recognition principles and practices - Beil, Frank J. ([New York, N.Y.] (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2013)
Revenue is the "top" line on the income statement and is the fundamental driver of business success. It is essential that managers and executives understand the complexities involved in recognizing revenue under Generally Accepted Accounting Principles (GAAP) in the US Revenue Recognition principles are , are primarily concerned with two things: (a) the timing aspect (the when issue) and (b) the amount to be recorded (the how much issue). This book will provide extensive guidance in assisting managers with the appropriate answers to the two questions above for their companies. This book is principally designed for managers and executives who have organizational responsibility for delivering results in the form of "profits" for their organizations. The book will be a comprehensive yet readable examination of the existing rules of revenue recognition for corporate entities. After reading the book, the manager or executive will have a thorough understanding of how accountants measure and record revenue. This "skill-set" will prove invaluable in understanding the impact that their business decisions will have on the financial statements with an emphasis on the income statement and the statement of cash flows. The book will also have an executive-level overview of the proposed "IASB and FASB Standard: Revenue from Contracts with Customers."
Examples index -- 1. The big picture: fundamental concepts -- 2. Multiple-element arrangements -- 3. Product revenue -- 4. Service revenue -- 5. Revenue from contracts with customers -- Notes -- References -- Index.
Part of: 2013 digital library.
Includes bibliographical references (p. 143-144) and index.
Also available in print.
Mode of access: World Wide Web.
System requirements: Adobe Acrobat reader.
Title from PDF t.p. (viewed on April 29, 2013).
Keywords: Revenue -- Accounting; arrangements; fixed or determinable; stand-alone value; deliverables; variable consideration; performance obligations; rights of return; performance models; customer acceptance; allocation; multiple element arrangement; revenue recognition; completed performance; proportional performance; product revenue; service revenue; contracts with customers